2022
DOI: 10.1155/2022/9689769
|View full text |Cite|
|
Sign up to set email alerts
|

Construction of Community Medical Communication Service and Rehabilitation Model for Elderly Patients under the Internet of Things

Abstract: The objective of this study was to discuss the health management of elderly patients in the community and the management of community rehabilitation under the support of the new Internet of Things (IoT). The IoT technology was adopted to monitor the wearable devices through mobile medical physiological data. The heart rate, blood pressure, respiratory rate, and other physiological indicators of the elderly were collected in real time. The support vector machine (SVM) algorithm was selected as the core algorith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Community rehabilitation health management emphasizes individualization [4] and community participation [5] to take appropriate health management measures based on the unique health needs of individuals and their disease risk [6] and ability to cope with disease risk [7] , and to develop individualized community rehabilitation health management plans to assess the various factors affecting health faced by individuals in order to intervene and improve the health status of users [8] . Wang Ying-qi explored the community rehabilitation health management model to carry out a five-level health management organization to give full play to the advantages of community hospitals in the hierarchical diagnosis and treatment of patients and provide comprehensive health management services for users [9] .…”
Section: Research and Analysis Of Community Rehabilitation Health Man...mentioning
confidence: 99%
“…Community rehabilitation health management emphasizes individualization [4] and community participation [5] to take appropriate health management measures based on the unique health needs of individuals and their disease risk [6] and ability to cope with disease risk [7] , and to develop individualized community rehabilitation health management plans to assess the various factors affecting health faced by individuals in order to intervene and improve the health status of users [8] . Wang Ying-qi explored the community rehabilitation health management model to carry out a five-level health management organization to give full play to the advantages of community hospitals in the hierarchical diagnosis and treatment of patients and provide comprehensive health management services for users [9] .…”
Section: Research and Analysis Of Community Rehabilitation Health Man...mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%